Authority of Regional Governments in Implementing Licensing After the Job Creation Law Entitles - Eki Furqon; Rizky Arifianto (International Journal of Law Society Services, 2025)
The enactment of the Job Creation Law is seen as strengthening centralization. "Some of the material contained in the Job Creation Omnibus Law has reduced the widest possible autonomy rights granted to regional governments, both provincial and district or regional authorities based on Article 18 paragraph (5) of the 1945 Constitution of the Republic of Indonesia (UUD NRI 1945)". This article intends to re-read the principles of decentralization related to the Authority of Regional Governments in Implementing Licensing After the Implementation of the Job Creation Law. The problem studied in this article is related to the concept of implementing licensing in the regions before and after the enactment of the Job Creation Law, whether the principle of decentralization is starting to shift back towards centralization through the authority of the central government in relation to regional authority in terms of business licensing in the regions. In this paper the author uses legal theories and statutory regulations related to this research. Then, in the research method for this article, the author uses the Normative Juridical Research Method (Legal Research). Since the enactment of the Job Creation Law, the flow of regional government towards recentralization has become stronger and Indonesia's regional autonomy has become increasingly questionable. "Some of the material contained in the Job Creation Omnibus Law has clearly reduced the widest possible autonomy rights granted to regional governments, both provincial and district based on Article 18 paragraph (5) of the 1945 Constitution of the Republic of Indonesia (1945 Constitution of the Republic of Indonesia). ". With the current enactment of the Job Creation Law, regional authority is only as a verifier of licensing files, so they do not have the authority to issue or not issue a permit, even though the background to the creation of this Law is to improve the investment ecosystem and regional business activities to encourage regional prosperity.